2020
DOI: 10.1186/s12891-020-03376-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance in dynamic movement tasks and occurrence of low back pain in youth floorball and basketball players

Abstract: Background: Prospective studies investigating risk factors for low back pain (LBP) in youth athletes are limited. The aim of this prospective study was to investigate the association between hip-pelvic kinematics and vertical ground reaction force (vGRF) during landing tasks and LBP in youth floorball and basketball players. Methods: Three-hundred-and-eighty-three Finnish youth female and male floorball and basketball players (mean age 15.7 ± 1.8) participated and were followed up on for 3 years. At the beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In this stage, 52 studies were excluded because they assessed other sports (n = 19), had different outcomes (n = 30), or were missing data (n = 3). Finally, 33 studies were included in this systematic review [ 6 , 7 , 8 , 10 , 11 , 16 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Table 2 ). Moderate interrater agreement (98%) was found between the two examiners.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this stage, 52 studies were excluded because they assessed other sports (n = 19), had different outcomes (n = 30), or were missing data (n = 3). Finally, 33 studies were included in this systematic review [ 6 , 7 , 8 , 10 , 11 , 16 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] ( Table 2 ). Moderate interrater agreement (98%) was found between the two examiners.…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles included, 69.7% of the studies obtained ethical approval (n = 23) [ 6 , 7 , 10 , 11 , 16 , 34 , 35 , 36 , 38 , 39 , 40 , 44 , 45 , 46 , 47 , 48 , 50 , 51 , 53 , 54 , 55 , 56 , 59 ] and 51.5% clearly reported that there were no conflicts of interest (n = 17) [ 6 , 7 , 10 , 11 , 16 , 33 , 34 , 36 , 37 , 38 , 45 , 46 , 50 , 51 , 53 , 56 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations